Study on structure–activity relationship of vitamin K derivatives: Conversion of the naphthoquinone part into another aromatic ring and evaluation of their neuronal differentiation-inducing activity. Issue 8 (15th April 2020) - Yoshimura, Hiroshi; Hirota, Yoshihisa; Soda, Seiya; Okazeri, Mayu; Takagi, Yuta; Takeuchi, Atsuko; Tode, Chisato; Kamao, Maya; Osakabe, Naomi; Suhara, Yoshitomo
Graphical abstract: Abstract: We synthesized novel vitamin K derivatives by converting the naphthoquinone group to benzene derivatives and benzoquinone. We evaluated their neuronal differentiation activities to investigate the effect of the quinone moiety on this process. We observed that the 1, 4-quinone as well as the side chain part play important roles in neuronal differentiation. We also performed QSAR analysis to predict the compounds which would have higher differentiation activity.